Analysis of Factors Related to the Stress Level of High School Students Facing the Covid-19 Endemic Era - Wijayanti, Anisa Catur; Umaroh, Ayu Khoirotul; Prihandana, Sadar; Khasanah, Devi Jantika Nur; Sari, Nur Ayu Sekar Arum (Jurnal Keperawatan, 2023)
Coronavirus Disease (COVID-19) is an infectious disease that attacks the respiratory system with its spread quite quickly and widely and the efforts made by the Indonesian government by implementing the Large-Scale Social Restrictions (PSBB) policy. The decrease in the incidence of Covid-19 in 2022 has led to changes in learning policies in schools that can increase the risk of stress in adolescents. This study aimed to analyze the relationship between age, sex, vaccine history, academic achievement, length of study, knowledge, attitudes, behavior, and screen time with stress levels in high school students. The study population was high school students from 4 schools in Surakarta and the sample used in this study was 605 respondents and was selected based on purposive sampling techniques. Data collection techniques using questionnaires and data analysis using Chi Square test. The results showed a relationship between sex (POR 2.619 CI: 1.881-3.647), knowledge (POR 0.691 CI: 0.492-0.970), behavior (POR 1.509 CI: 1.086-2.097), and there was no relationship between age, vaccine history, academic achievement, length of study, attitude, screen time with high school students' stress levels. High school students who are female, have less knowledge and behave less well are at risk of experiencing more severe stress. So it is necessary to provide accurate information about Covid-19 to high school students so that they can understand and contribute to making good Covid-19 prevention efforts.